IMPACT OF SOCIO-PSYCHOLOGICAL BARRIERS ON STRATEGIES EMPLOYED BY WOMEN LEADERS IN INFORMATION TECHNOLOGY SECTOR IN INDIA - Vidyakala, K.; Jennet, Raji; Nithyakala , K. (The journal of contemporary issues in business and government, 2021)
Leadership development for women plays an indispensable function in economic progress of India. The present study tries to analyze the relationship between sociological and psychological barriers on various strategies employed by women leaders in IT/ITeS Sector in Bengaluru and Coimbatore in India among 436 samples using a structured questionnaire consisting of 83 constructs. Smart PLS SEM was used to test theoretical framework since the present study tries to explore an area which is relatively less researched in India. The results of the study found the existence of statistically significant path between socio-psychological barriers and the strategies.